Wyrok Sądu Kościelnego we Włocławku (c. Grzęźlikowski) z 13.10.1997 r. w sprawie o nieważność małżeństwa z tytułu poważnego braku rozeznania oceniającego co do istotnych praw i obowiązków małżeńskich (kan. 1095, n. 2 KPK) - Grzęźlikowski, c. (Ius Matrimoniale, 2003)
Plaintiff brought a suit against his matrimony contracted with N. on 22nd of January 1984 in Saint Patrick's Cathedral in Auckland in New Zealand. N. in virtue of lack of judging discernment regarding matrimonial rights and duties on his side (can. 1095, 2 Code of Canonical Proeedings) suggesting that in was caused by fact that being on emigration in New Zealand, missing the country of origin and family, being mentally woebegone and being depressed, he had restricted will and critical cognizance and was not able to have evaluotion of matrimonial agreement subject and its free choice. He also thought that because of arisen situation and due to his individualistic immaturity in moment of contracting the matrimony, he had lack of judging discernment regarding the matrimonial rights and dubes. He lodged a complaint for nullity of marriage to the tribunal of his place of residence in March 1996. Defendant was living in England in that time. Tribunal Włocławek obtained - acco rding to canonic regulations 1673, 4 Code of C nonical Proceedings - a permission to wunduct a case from the tribunal of defendant's place of residence. Hearing of evidence induded hearing of the parties, witnesses and examination of the plaintiff by psychologist expert appointed by the wurt, who issued an opinion. Confronting the legal motives submitted in case with actual real motives, after taking the cognizance of plaintiffs notes after publishing the files of a case and before – sentence notes of the defender of matrimonial union, the board of judges passed a sentence in favour of validity of appealed marriage. It was found that: 1. plaintiff could be really actually mentally depressed, emotionally trembling, he missed his country and family, however that state was not as strong and serious to make him not to realize the fact of what the marriage was; 2. facts that he left Poland by himself and chose emigration by himself indicate that he was self-dependent and individualistically mature; 3. lack of discernment was not confirmed by testimonies of defendant and witnesses as well as circumstances of marriage contracting, its course and actual reasons of marriage breakdown; 4. expert appointed by the court found the plaintiff individualistically mature and found no reasons that would cause the plaintiff to have of ability of due judgment of what the matrimony is and which obligations it put him under as well as ability to express matrimonial consent; 5. plaintifs cognitive and volitive powers were able to evaluate correctly the resulted situation, correctly express matrimonial consent and express matrimonial consent in correct and volid way. Second Instance Tribunal from Gniezno confirmal a sentence of Tribunal form Włocławek suggesting the plaintiff to possibly lodge a complaint for nullity of marriage in virtue of simulation of matrimonial condent on his side.